Tuberkulosis Multidrug-Resistant (TB-MDR): Diagnosis and Treatment - Baiq Ayu Rahmawati; Rina Lestari (Lombok Medical Journal, 2024)
Multidrug-Resistant Tuberculosis (MDR-TB) is a TB disease that is resistant to rifampicin and isoniazid with or without other first-line Anti-Tuberculosis Drugs (OAT). Accurate MDR-TB diagnosis and treatment methods are very important to minimize the impact of the disease. The aim of this literature review is to increase understanding of MDR-TB, with a focus on discussing methods of diagnosing and treating MDR-TB. Diagnosis in MDR-TB patients can be done using TCM and sensitivity testing using the Line-2 LPA (Line Probe Assay) method or conventional methods. Treatment is in the form of the use of bedaquiline, prothionamide, linezolid, and moxifloxacin regimens for 6 months; all-oral regimen for 9 months; and long-term regimens for MDR-TB patients